Different Floor Management Systems Affect Soil Properties and Initial Development of Apple Tree (Malus × domestica Borkh.) in an Orchard - Sebastian Przybyłko; Ewa Szpadzik; Jacek Marszał; Wojciech Kowalczyk; Dariusz Wrona (Agriculture, 2022)
In order to achieve sustainable food production, non-chemical weed management practices need to be developed for fruit growing. Tailor-made floor management systems enable efficient weed regulation, but they also affect the soil quality in an orchard. In this article, the effects of various floor management systems in a ‘Red Jonaprince’ apple (Malus × domestica Borkh.) orchard on the soil properties and the trees’ nutritional status and initial development during the first two years after the orchard’s establishment were assessed. The experiment was set up in the spring of 2017 in the Experimental Orchard of WULS. ‘Red Jonaprince’ cv. trees grafted on M.9 rootstock were planted with 3.5 × 1 m spacing between them. Different floor management systems were applied to the rows, including the selected organic mulches: Miscanthus × giganteus straw (MG1 and MG2), spent mushroom substrates (SMS1 and SMS2), herbicide strip (HS), clear mechanical soil cultivation (MC), and synthetic black mulch (BC). The organic mulches affected the soil properties significantly. Spent mushroom substrates (SMS1, SMS2) increased the P and K contents in the soil, increased the salinity 10-fold, and retarded the growth in terms of the trunk cross-section area (TCSA) and its increment compared with other systems. Miscanthus × giganteus straw mulch (MG1, MG2) was associated with a more vigorous shoot growth compared with other combinations in the first year of the study as it provided a better tree nitrogen nutritional status. The floor management system affected the generative development of the trees. Mulching with a spent mushroom substrate boosted the flower bud formation intensity, but it did not affect the yielding quantity. Moreover, due to the poor fruit set, the trees mulched with a spent mushroom substrate (SMS2) gave a low initial bearing. High crop loads were noted for the trees treated with black synthetic mulch (BC) and the trees mulched with Miscanthus × giganteus straw (MG1). This was an effect of the tree size rather than the blooming intensity, while there were no differences in the cropping efficiency index (CEI) parameter.